Global, regional, and national burden of dengue, 1990–2021: Findings from the global burden of disease study 2021 - Shun-Xian Zhang; Guo-Bing Yang; Ren-Jie Zhang; Jin-Xin Zheng; Jian Yang; Shan Lv; Lei Duan; Li-Guang Tian; Mu-Xin Chen; Qin Liu; Yu Wang; Xiao-Jie Hu; et al. (Decoding Infection and Transmission)
Background: Dengue is an acute viral infectious disease caused by the dengue virus and transmitted through mosquitoes. Although numerous studies have examined the global burden of dengue, comprehensive and systematic global analyses remain limited. This study uses data from the Global Burden of Disease (GBD) Study 2021 to systematically analyze the global epidemiological trends and disease burden of dengue from 1990 to 2021. Methods: This study utilized data from the GBD Study 2021 Study to analyze trends in the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of dengue across 204 countries and territories, stratified by age, sex, and Socio-demographic Index (SDI) levels. In addition, a Bayesian age-period-cohort model was employed to predict the future burden of dengue. The average annual percent change (AAPC) was used to describe the overall trend in rates or counts of indicators between 1990 and 2021. Results: In 2021, the global ASIR of dengue was 752.04 per 100,000 population (95 % UI: 196.33–1363.35), and ASMR was 0.38 per 100,000 population (95 % UI: 0.23–0.51). From 1990 to 2021, both the ASIR (AAPC = 7.89, 95 % CI: 7.89–8.91) and ASMR (AAPC = 0.01, 95 % CI: 0.00–0.01) showed an increasing trend. Adolescents under 14 years had the highest ASIR, age-standardized prevalence rate (ASPR), and age-standardized disability-adjusted life years (DALYs) for dengue. By 2035, the projected ASIR of dengue is 862.23 per 100,000 population (95 % CI: 627.84–1096.62 per 100,000 population), the ASPR is 51.60 per 100,000 population (95 % CI: 37.70–65.50 per 100,000 population), and the ASMR is 0.43 per 100,000 population (95 % CI: 0.29–0.56 per 100,000 population). The ASIR, ASPR, ASMR, and age-standardized DALYs for dengue are expected to continue rising in the next 10 years. Conclusion: The global burden of dengue is projected to continue rising in the coming years, underscoring the urgent need for comprehensive control measures, including enhanced vector control, public education, vaccination, and drug development. These findings provide crucial scientific evidence for the formulation of effective public health strategies and interventions aimed at reducing the global threat posed by dengue.